Rural-Urban Migration with Behavioral Preferences - Dafeng Xu (European Regional Science Association (ERSA), 2014)
This paper incorporates the behavioral labor economic perspective into the traditional Harris-Todaro rural-urban migration model. We study cases in which one's utility is not only determined by his own wage, but also by wages of others. In our theoretical models, rural-urban migration is driven by the expected utility differential, instead of the expected wage differential. We find that the conventional 'Harris-Todaro equilibrium' (in which the rural wage equals the expected urban wage) always exists, but there are two other possible equilibria, in which the rural wage can be either greater or less than the expected urban wage. Moreover, we show that if lower-income players gain utility from the wage differential, i.e., they are altruistic towards higher-income players, and the degree of altruism is sufficiently large, then the two equilibria in which the rural wage differs from the expected urban wage are stable, and the Harris-Todaro equilibrium is not stable.
Keywords: O15; P25; D64; J46; 330